A Comparison of the Effectiveness of Intensive Short-Term Dynamic Psychotherapy (ISTDP) and Acceptance and Commitment Therapy (ACT) on Psychological Distress and Ego Strength in Women Victims of Domestic Violence - Shokohifar, Sahar; Mahdian, Hossein; Ghasemi Motlagh, Mehdi (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to compare the effectiveness of Intensive Short-Term Dynamic Psychotherapy (ISTDP) and Acceptance and Commitment Therapy (ACT) on reducing psychological distress and enhancing ego strength in women victims of domestic violence.Methods and Materials: This quasi-experimental study employed a pretest-posttest-follow-up design with a control group. Forty-five women aged 20 to 45 who had experienced domestic violence and met the inclusion criteria were selected purposefully from counseling centers in Gorgan, Iran, and randomly assigned into three groups: ISTDP (n = 15), ACT (n = 15), and control (n = 15). Participants completed the Depression Anxiety Stress Scales (DASS-21) and the Ego Strength Scale (ESS) before and after the interventions and again at a three-month follow-up. The ISTDP intervention was administered in 15 individual sessions, and the ACT protocol was delivered in 8 individual sessions. The control group was placed on a waitlist. Data were analyzed using repeated measures multivariate analysis of variance (MANOVA) and Bonferroni post hoc tests.Findings: The results indicated significant effects of time on psychological distress variables including depression (F = 102.07, P < .001), anxiety (F = 33.70, P < .001), and stress (F = 72.75, P < .001), and on ego strength dimensions such as ego control (F = 48.57, P < .001), resilience (F = 18.59, P < .001), mature defenses (F = 79.95, P < .001), problem-focused coping (F = 28.23, P < .001), and emotion-focused coping (F = 30.55, P < .001). However, no significant differences were found between the ISTDP and ACT groups (P > .05) in any of the outcome variables.Conclusion: Both ISTDP and ACT were equally effective in significantly reducing psychological distress and improving ego strength in women victims of domestic violence, and their benefits were sustained at follow-up. These findings support the use of either therapy in trauma-focused clinical interventions.